Work, mobility, and participation : - Cole, Robert E. (University of California Press, 1979)
A comparative study of American and Japanese industry, focusing on job mobility, the relationship between employer and employee in the decision-making process, and the work ethic. The analysis is based on case studies of labor conditions in Detroit and Yokohama. Cole stresses the influence of differing social, political and economic conditions on the workplace in the two countries.